Constructing war accounts in Malaysia / Che Mahzan Ahmad and Syafini Samsudin - Ahmad, Che Mahzan; Samsudin, Syafini (Centre for Media and Information Warfare Studies, 2008)
With reference to the mediation, the 'accounted narrativised news' are expected to be interactively developed and modified (Cobb 1994) with the reality of the concerned life-world (Nasser 1983, Lendvai 1983, Wiio 1983, Karch 1983). In this reality, understanding and construction of news are related to contextualized or configured knowledge, which means a particular event is understood upon being located in a narrative sequence of the significant order of representation. The narrativised news in this regard is news that has been authored within a specific frame of reference and point of view. This work concerns the narrativised news about the Gulf War in 2003 as accounted in Utusan Malaysia and New Straits Times. Utusan Malaysia is a leading Malay language newspaper in Malaysia while New Straits Times is the influential English language newspaper of the country.